Antecedent and Consequences of Mall Value - Salman Faris Insani; Ariyani Wahyu Wijayanti; Usman Sudarmaji; Maria Joy I. Idian (Journal of Management Studies and Development, 2022)
This research contributes by using the concept and measurement of mall values to increase generalization, and to connect it with antecedent variables and their consequences. Variables measured in relation to the mall value concept in this study are shopping environments and consumer satisfaction. The respondents in this study were 210 mall shoppers at Hartono Lifestyle Mall Surakarta. The empirical results indicate mall value construct is an important issue on marketing strategy crafting in Hartono Lifestyle Mall Surakarta.